Jumpstarting the Onion Omega2 : an introduction to a new low-cost Internet of things computer - Donat, Wolfram (Maker Media, Inc., 2018)
Get up and running quickly with the Jumpstarting series!Jumpstarting books provide an avenue for makers to quickly master topical knowledge. Each book starts with instructions on how to install or initialize the hardware or software needed to reach the all-important "Hello, World" stage of getting started. The second project builds on the first to use more of the hardware or software's capabilities. The final project expands the user's knowledge into lesser-known aspects of the topic. All Jumpstarting projects are for Makers -- they provide hands-on, real-world experience in making the hardware or software do what you want it to do.